2020
DOI: 10.1002/jmv.26591
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SARS‐CoV‐2 mutations in Mexico, Belize, and isolated regions of Guatemala and its implication in the diagnosis

Abstract: The genomic sequences of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) worldwide are publicly available and are derived from studies due to the increase in the number of cases. The importance of study of mutations is related to the possible virulence and diagnosis of SARS‐CoV‐2. To identify circulating mutations present in SARS‐CoV‐2 genomic sequences in Mexico, Belize, and Guatemala to find out if the same strain spread to the south, and analyze the specificity of the primers used for diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
(94 reference statements)
0
20
0
1
Order By: Relevance
“…This approach has been reported previously to detect other virus mutations with clinical importance, such as the ones in the influenza virus (Bolotin et al, 2009;van der Vries et al, 2010;Wong et al, 2011;Hoang Vu Mai et al, 2019). A similar screening was also performed by analyzing SARS-CoV-2 mutations and evaluating their diagnosis implication (Hernańdez-Huerta et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…This approach has been reported previously to detect other virus mutations with clinical importance, such as the ones in the influenza virus (Bolotin et al, 2009;van der Vries et al, 2010;Wong et al, 2011;Hoang Vu Mai et al, 2019). A similar screening was also performed by analyzing SARS-CoV-2 mutations and evaluating their diagnosis implication (Hernańdez-Huerta et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Another concern is a variant detected in France of a S deletion (ΔH69-V70) which has shown to be associated with S-gene target gene detection failure in three-target RT-PCR [48]. Several reports have targeted mutations in different open reading frames (ORFs) especially ORF8 position which was found in some isolates from Mexico, Belize and Guatemala as potentially leading to epitope loss and reduced sensitivity for serological testing [49][50][51].…”
Section: Decreased Diagnostic Sensitivitymentioning
confidence: 99%
“…Previous in vitro and simulation studies have found that G614 mutation is considered as more infectious variant than the D614 wildtype (Daniloski et al, 2020;Hou et al, 2020;Hu et al, 2020;Korber et al, 2020;Li et al, 2020;. Studies showed that D614G mutation is associated with antigenic epitopes (Gupta et al, 2020;Hernández-Huerta et al, 2020;Islam et al, 2020;Kim et al, 2020;Koyama et al, 2020;Saha et al, 2020; . CC-BY-NC 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 19, 2021. ; https://doi.org/10.1101/2021.04.12.21255337 doi: medRxiv preprint 9 2020), antibody neutralizing sensitivity (Goldman et al, 2020;Hu et al, 2020;Klumpp-Thomas et al, 2020;Li et al, 2020;Mansbach et al, 2020), infectivity (Daniloski et al, 2020;van Dorp et al, 2020;Hu et al, 2020;Korber et al, 2020;Li et al, 2020), transmission (van Dorp et al, 2020 and fatality (Hernández-Huerta et al, 2020). Plante et al 2020 have suggested that SARS CoV-2 G614 variant has roles in increasing upper respiratory viral loads, transmissions and survival fitness of the virus (Plante et al, 2020).…”
Section: Discussionmentioning
confidence: 99%